DESIGN AND SYNTHESIS OF NOVEL 1-((DIMETHYLAMINO)METHYL)-3-(4-(3-(SUBSTITUTE DPHENYL)-4-OXOTHIAZOLIDIN-2-YL)PHENYLIMINO)-5-NITROINDOLIN-2-ONES AS POTENT ANTITUBERCULAR AGENTS - KOSARAJU LAHARI; RAJA SUNDARARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Isatins have emerged as antimicrobial agents due to their broad spectrum of in vitro and in vivo antimicrobial activities. In addition, thiazolidinone also reported to possess various biological activities particularly antimicrobial activity. Due to the importance, we planned to synthesize compounds with isatin functionality coupled with thiazolidinone as possible antitubercular and antimicrobial agents which could furnish better therapeutic results. Methods: In vitro Mycobacterium tuberculosis method and agar streak dilution test are used to estimate antitubercular and antimicrobial potency of title analogs, respectively. Minimum inhibitory concentration of entire title compounds was determined against all tested microorganism such as M. tuberculosis, four Gram-positive, three Gram-negative bacteria, and two fungi. Results: A series of new thiazolidinone substituted Schiff and Mannich bases of 5-nitroisatins were designed and synthesized by a multistep synthesis from isatin. Structures of synthesized compounds are characterized using Fourier-transform infrared, proton nuclear magnetic resonance, mass spectroscopy, and bases of elemental analysis. Mild to good antitubercular and antimicrobial activity was showed by synthesized 5-nitroisatin analogs. The relationship between the biological activity and the functional group variation of the tested compounds was discussed. Conclusion: 3-(4-(3-(4-Aminophenyl)-4-oxothiazolidin-2-yl)phenylimino)-1-((dimethyl amino)methyl)-5-nitroindolin-2-one 6 and 3-(4-(3- (2-aminophenyl)-4-oxothiazolidin-2-yl)phenylimino)-1-((dimethylamino)methyl)-5-nitroindolin-2-one 13 were found to be the most potent compounds of this series which might be extended as a novel class of antimicrobial agents.